Tsangaya System of Education and its Positive Effects on Almajiri and Society in Potiskum, Yobe State Nigeria - Idriss, Ibrahim Dahiru; Hamzah, Norhayati Hj (Journal of Al-Tamaddun, 2021)
Tsangaya System of Education, generally called Makarantan Allo or traditional Qur’anic school has been in existence for decades, its history can be traced back to the early days of the coming of Islam to Nigeria. It has been a source of moral and scholastic training of the Muslim dominated societies in the northern part of Nigeria. The system which provides essentially, basic Qur’anic education to the Almajiri (students) has contributed tremendously in promoting Qur’anic education, inculcating self-discipline, spiritual growth of Muslim individuals and the communities. Therefore, this article examines the positive effects of Tsangaya System of Education on the Almajiri in Potiskum Yobe State, Nigeria. The study employed a qualitative approach that entails the techniques of documentation and interviews in collecting data while thematic analysis was utilized for data analysis. The findings revealed that Tsangaya System of Education in Potiskum area of Yobe State has positive effects on the Almajiri in the area such as mastering the recitation, memorization and writing of the glorious Qur’an as well as inculcating good behavioural modes.